Organic Antifungal Drugs and Targets of Their Action - Maksimov, Alexander Y.; Balandina, Svetlana Yu; Topanov, Pavel A.; Mashevskaya, Irina V.; Chaudhary, Sandeep (Current Topics in Medicinal Chemistry, 2021)
In recent decades, there has been a significant increase in the number of fungal diseases. This is due to a wide spectrum of action, immunosuppressants and other group drugs. In terms of frequency, rapid spread and globality, fungal infections are approaching acute respiratory infections. Antimycotics are medicinal substances endorsed with fungicidal or fungistatic properties. For the treatment of fungal diseases, several groups of compounds are used that differ in their origin (natural or synthetic), molecular targets and mechanism of action, antifungal effect (fungicidal or fungistatic), indications for use (local or systemic infections), and methods of administration (parenteral, oral, outdoor). Several efforts have been made by various medicinal chemists around the world for the development of antifungal drugs with high efficacy with the least toxicity and maximum selectivity in the area of antifungal chemotherapy. The pharmacokinetic properties of the new antimycotics are also important: the ability to penetrate biological barriers, be absorbed and distributed in tissues and organs, get accumulated in tissues affected by micromycetes, undergo drug metabolism in the intestinal microflora and human organs, and in the kinetics of excretion from the body. There are several ways to search for new effective antimycotics: - Obtaining new derivatives of the already used classes of antimycotics with improved activity properties. - Screening of new chemical classes of synthetic antimycotic compounds. - Screening of natural compounds. - Identification of new unique molecular targets in the fungal cell. - Development of new compositions and dosage forms with effective delivery vehicles. The methods of informatics, bioinformatics, genomics and proteomics were extensively investigated for the development of new antimycotics. These techniques were employed in finding and identification of new molecular proteins in a fungal cell; in the determination of the selectivity of drugprotein interactions, evaluation of drug-drug interactions and synergism of drugs; determination of the structure-activity relationship (SAR) studies; determination of the molecular design of the most active, selective and safer drugs for the humans, animals and plants. In medical applications, the methods of information analysis and pharmacogenomics allow taking into account the individual phenotype of the patient, the level of expression of the targets of antifungal drugs when choosing antifungal agents and their dosage. This review article incorporates some of the most significant studies covering the basic structures and approaches for the synthesis of antifungal drugs and the directions for their further development.
Keywords: Antibiotics